The meaning and content marketing technology - Бейжанова A.; Ахметова, З. (Journal of Economic Research & Business Administration, 2017)
The article deals with the issues related to improving the efficiency of business entities by technologizing process of marketing activities, content and value of marketing technologies at the present stage. Been described importance, content, features and properties of marketing technologies. Are determined basic factors underlying the marketing of technology, in particular, crushing the marketing process into separate procedures and operations, with the subsequent regulation of performing the procedures and operations. The special attention is paid to the types of marketing technology. A market is a place where the marketing technologies and innovative service strategies start developing. Also in the article the theoretical aspects of marketing technology tools, including public relations tools, analyzes the methods of promotion, the necessity of using the theoretical, methodological and administrative principles of marketing technology. In the process of writing the article identified the most important characteristics of modern marketing techniques, such as the orientation of marketing technologies for strategic development. Аlso identified the strengths and weaknesses of the innovative marketing technology.